A fatal familial insomnia patient newly diagnosed as having depression: A case report. Issue 41 (15th October 2021) - Yukang, Tan; Jiaquan, Liang; Xiaoling, Li; Yiliang, Liu; Guohong, Xu; Caixia, Xu; Guojun, Xie
Abstract: Introduction: Fatal familial insomnia (FFI) is a rare clinical case. The study was mainly to report the clinical symptoms and imaging and genetic characteristics of a FFI case with depression, with relevant literature summarized. Patient concerns: A male, aged 57 years old, with mental disorders and progressive memory decline one year before admission. Diagnosis: Clinical manifestations: he had obvious abnormal mental behavior, rapidly progressing dementia symptoms, stubborn insomnia, abnormal movements and laryngeal stridor after falling asleep at night. Imaging and genetic test results: the cranial magnetic resonance imaging showed frontal temporal lobe atrophy; the polysomnography results showed no effective sleep; the 14-3-3 test result of cerebrospinal fluid was negative; the prion protein (PRNP) test showed that the D178N gene locus had mutations. And the patient was finally diagnosed as FFI. Interventions: There were no obvious effects in the treatment using medicines such as Risperidone, Olanzapine, Alprazolam, Clonazepam, and Deanxit. Outcomes: Mobility dysfunction of the patient was further aggravated. He was no longer able to move around on his own, and there were serious mental disorders. Conclusion: PRNP examination is of guiding significance for the diagnosis of the FFI of depression. Hence, it is very necessary to perform PRNP examination in clinical diagnosis of FFI of depression.